Green Entrepreneurial Intention Through Green Economy For Developing Student Entrepreneurial Character in Selangor, Malaysia - Ikhtiari, Kirana; Azis, Dian Eka Pusvita; Ramadani, Dinda; Putri F, Annisa Aulia Utami (STIE Amkop Makassar, Indonesia, 2024)
This research analyzes the effectiveness of the International Community Service Program in increasing interest in green entrepreneurship among students of Universiti Kebangsaan Malaysia (UKM), Selangor. The program used two methods: online in the form of a green entrepreneurship seminar through Zoom and offline in a sharing session at the Tun Sri Lanang UKM Library. Through education and training, the program aimed to raise partners' awareness of the importance of protecting the environment and encourage them to start green businesses to support the green economy and Sustainable Development Goals (SDGs). Results showed that the program effectively fostered partners' interest and awareness of green business. Participants were actively engaged in discussions, indicating that online and face-to-face methods effectively introduced green entrepreneurship. In addition, participants gained insight into the opportunities and challenges of green business and guidance on developing an environmentally friendly business plan. This research enriches the green entrepreneurship literature by testing the effectiveness of green entrepreneurship training. Managerially, it offers an educational program model that combines environmental and entrepreneurial aspects. The program is suggested to be a workshop on making recycled products, providing hands-on skills for green entrepreneurship practice.